TEACHING FOREIGN LANGUAGES FOR PRESCHOOL CHILDREN - Muxammadyusupova Nozimaxon (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Over the past few years, learning a foreign language has become as impossible of self-development as I’m about to. A foreign language has become a mandatory component of education not only in schools and universities, but also in many preschool institutions. This article provides information on effective ways and methods of teaching English to young children quickly and easily. In this article, you can get acquainted with meaningful and interesting methods of teaching English in preschool education and primary classes using modern information technologies and game methods.